A review of code smell mining techniques. Issue 11 (9th September 2015) - Rasool, Ghulam; Arshad, Zeeshan
Abstract: Over the past 15 years, researchers presented numerous techniques and tools for mining code smells. It is imperative to classify, compare, and evaluate existing techniques and tools used for the detection of code smells because of their varying features and outcomes. This paper presents an up‐to‐date review on the state‐of‐the‐art techniques and tools used for mining code smells from the source code of different software applications. We classify selected code smell detection techniques and tools based on their detection methods and analyze the results of the selected techniques. We present our observations and recommendations after our critical analysis of existing code smell techniques and tools. Our recommendations may be used by existing and new tool developers working in the field of code smell detection. The scope of this review is limited to research publications in the area of code smells that focus on detection of code smells as compared with previous reviews that cover all aspects of code smells. Copyright © 2015 John Wiley & Sons, Ltd.